Hipoclorito de sodio (NaCLO) en la alcalinidad de jabón de tocador artesanal a base de aceite residual Post-Fritura. - Gilces González, César Eduardo (2018)
The objective of this research was to determine the percentages of sodium hypochlorite (NaClO) to obtain the ideal alkalinity of a handmade toilet soap, using as raw material post-frying oil, governed by the requirements for liquid soap of the Ecuadorian technical Standard (INEN 0841) in force. A DCA experimental design or linear model was used in the arrangement of a single factor. The factors under study were: A: Percentages of 17% bleach (red seal) diluted in aqueous solutions at (20%, 21% 22%, 235 and 24%%) respectively; Percentage of frying oil (60%); Percentage of 21% alcohol at 99 °. We analyzed the variables free alkalinity (AL), Total alkalinity (at), matter insoluble in alcohol (MIA), matter insoluble in water (MIH2O), chlorides (C), and PH. The results showed significant differences (p < 0.05) for each of the factors in study as in their interaction. With the results obtained in the statistical program IBM SPSS (free version), it was established that the treatment was T2 (60% of oil, 21% alcohol, 17% aqueous solution Al (21%)) respectively in M. I. A and alcohol, in terms of chloride and alkalinity free and total no treatment is justified to the requirements detailed by the current standard INEN NTE 0841, in addition to that the T2 had a pH of 6.3. Depending on the factors studied, they have a negative influence on the response variables. It is concluded that none of the treatments meet the requirements of the standard INEN 0841.